Produção de cebola em solo salinizado - Lima, Maria D. B.; Büll, Leonardo Theodoro [UNESP] (FapUNIFESP (SciELO), 2008)
The use of water or soil with a high salt concentration has been the main cause of failure in the yield of many crops. Consequently, this work aimed at evaluating the effects of different salinity levels and soil moisture on onion yield (cultivar Baia periforme). An experiment was conducted in a greenhouse of the Soil Science Department - FCA - UNESP, Botucatu, SP, in pots of 10 L. The soil was salinized with NaCl in order to increase the electrical condutivity of saturation extract of soil from 0.13 to 2; 4; 6 and 8 dS m-1. In each experimental unit 15.2 g of thermophosphate enriched by micronutrients and 1.5 L of organic matter were incorporated. The moisture treatments kept the soil within the limits of 25-50, 50-75 and 75-100 % of field capacity. The plant height the pseudostem diameter and yield of bulbs were evaluated. The results lead to the conclusion that the salinity reduced the vegetative growth and the yield of onion bulbs. Moisture treatment influenced both the diameter and weight of bulbs. The water consumption of the plants decreased with increassing soil salt concentration.
Onion production in salinized soil
Keywords: Allium cepa; Salinity; Water stress